Ruthenium(II) MOCVD Precursors for Phosphorus‐Doped Ruthenium Layer Formation. Issue 17 (22nd April 2020) - Preuß, Andrea; Tamuliene, Jelena; Madajska, Katarzyna; Szymanska, Iwona B.; Korb, Marcus; Rüffer, Tobias; Jeschke, Janine; Melzer, Marcel; Bankwitz, Jörn; Schulz, Stefan E.; Lang, Heinrich
Abstract : The synthesis and solid‐state structure of Ru(CO)2 (PEt3 )2 (O2 CR)2 (4a –f, R = Me, Et, i Pr, t Bu, CH2 OMe, CF3 ) is reported. The vapor pressure of 4a –f was measured, ranging from 6.3 mbar (4f ) to 14.8 at 190 °C (4e ). Complexes 4a –f decompose between 210–350 °C of which 4c shows the lowest (248 °C) and 4e (280 °C) the highest onset temperature. TG‐MS studies (4f ) showed subsequent decarbonylation and decarboxylation processes. To determine the gas phase composition VT IR studies were performed. Based on TG‐MS, VT IR and DFT calculations decomposition mechanisms are discussed. Complexes 4a –f are suited as MOCVD precursors, producing dense layers of 25–50 nm thickness, consisting of 57 at‐% Ru, up to 18.2 at‐% P and as impurities C, N and O. A carbon‐free Ru(P) layer was obtained with 4a as CVD precursor. Abstract : A series of ruthenium complexes of general type Ru(CO)2 (PEt3 )2 (O2 CR)2 was synthesized and characterized regarding their thermal behavior. Furthermore, the decomposition mechanisms of the complexes were investigated by TG‐MS, VT IR, and DFT calculations. The compounds were used for the deposition of Ru(P) thin films via the CVD process, affording layers with 57 at‐% Ru and up to 18.2 at‐% P.